2020
DOI: 10.3389/fmicb.2020.00471
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypical Characteristics of the Black Yeast Exophiala dermatitidis Are Affected by Pseudomonas aeruginosa in an Artificial Sputum Medium Mimicking Cystic Fibrosis–Like Conditions

Abstract: Research into the cooperative pathogenicity of microbes in cystic fibrosis (CF) lungs is crucial for an understanding of the pathophysiology of infections and the development of novel treatment strategies. This study investigated the impact of the common CFassociated bacterial pathogen Pseudomonas aeruginosa on the black yeast Exophiala dermatitidis. It evaluated the planktonic growth, biofilm formation, morphology, and virulence of the fungus in the presence or absence of P. aeruginosa. It also determined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
(78 reference statements)
1
5
0
Order By: Relevance
“…The filamentation of C. albicans was also strongly reduced in the presence of P. aeruginosa over time. Similar effects have been reported for co-culture experiments of P. aeruginosa and the black yeast Exophiala dermatitidis in cystic fibrosis (CF)-like environment, and it was shown that the quorum-sensing molecules N-acyl homoserine lactone (AHLs) of P. aeruginosa play a major role in this phenotype ( 55 ).…”
Section: Resultssupporting
confidence: 62%
“…The filamentation of C. albicans was also strongly reduced in the presence of P. aeruginosa over time. Similar effects have been reported for co-culture experiments of P. aeruginosa and the black yeast Exophiala dermatitidis in cystic fibrosis (CF)-like environment, and it was shown that the quorum-sensing molecules N-acyl homoserine lactone (AHLs) of P. aeruginosa play a major role in this phenotype ( 55 ).…”
Section: Resultssupporting
confidence: 62%
“…Therefore, use of host-like conditions in microbial susceptibility testing, including biofilm-related tolerance, supports in identifying specific drug targets, as well as unraveling the bacterial physiology, along with physiological and metabolic basis of biofilm formation [ 61 , 68 ]. By using this approach, growth, biofilm formation, and antimicrobial tolerance have not only been assessed for P. aeruginosa , but also for other microorganisms colonizing the cystic fibrosis lung, including Stenotrophomonas maltophilia , Mycobacterium abscessus, and black yeast [ 69 , 70 , 71 ]. It is worth mentioning that the antimetabolite oxythiamine was initially identified as an antimicrobial agent in artificial sputum medium, showing synergistic effects in combination with tetracycline for which P. aeruginosa is intrinsically resistant [ 72 ].…”
Section: Assessment Of Antimicrobial Tolerance Mimicking the Host Milieumentioning
confidence: 99%
“…Ammonium is completely consumed in many ecosystems, but where isotope effects are permitted to be expressed ( e.g. , anoxic sediments and waters/ocean basins), its δ 15 N is thought to reflect the balance between N fixation, with a 15 ε near 0‰; aerobic ammonia oxidation, with a variable isotope effect between 14‰ and 46‰ 14 17 ; and assimilation (4‰ to 27‰) 18 . For anammox, a very limited number of isotope studies have constrained 15 N/ 14 N isotope effects in enriched cultures 10 , 19 , while one study has estimated their values in wastewater incubations 20 .…”
Section: Introductionmentioning
confidence: 99%